Karakteristik Pasien Fracture Supracondyler Humerus pada Anak-Anak di RSUP Sanglah Tahun 2019-2020 - Wijayanti, Sinar Adhy (E-Jurnal Medika Udayana, 2022)
Humeral supracondylar fracture is a fracture that occurs at the elbow, precisely at the distal part of humeral bone as high as the humeral epicondyle which passes through the olecranial fossa. Humeral supracondylar fracture is a common fracture occur in the pediatric, 18% of all fractures experienced by children. The aims to determine the characteristics of supracondylar humeral fractures in children Sanglah Hospital Denpasar in 2019-2020. Research use descriptive method with cross-sectional study. Determination of samples based on inclusion and exclusion criteria. Data analyzed using SPSS 26 software to obtain characteristics of patient humeral supracondylar fractures based on age, sex, fracture classification, location of the incident, onset, management, and complications. The results showed that cases of humeral supracondylar fractures in children at Sanglah Hospital Denpasar in 2019-2020 there are 16 cases. Humeral supracondylar fractures mostly occurred in 5-9 year age group (62.5%), dominated by male sex (62.5%). The most common classification of fractures is Gartland type III with percentage of 56.3%. Most of samples had fractures when they fell at home (62.5%) with acute onset of 93.8%. Most of samples received operative management of 68.8% and 93.8% did not experience complications. This research useful because can provide perception about characteristics of patients with supracondylar humeral fractures in children at Sanglah Hospital Denpasar 2019-2020. Analytical research needed to understand the relationship between characteristic variables of supracondylar fractures. Keywords : Humeral Supracondylar Fracture, Characteristic, Children.